Low-friction-coefficient plastic, production process and low-friction-coefficient plastic product

Through multi-stage responsive three-layer structure microcapsule technology and multi-phase interface regulation, combined with gradient crosslinking network and electric field-assisted directional treatment, a low-coefficient plastic was prepared, which solved the problem that existing materials were difficult to achieve low friction coefficient, low atomization performance and stable lubrication in a wide temperature range at the same time, and achieved excellent friction performance, mechanical performance and environmental adaptability.

CN119798859AInactive Publication Date: 2025-04-11HUNAN ZHONGCHUANG PACKAGING CO LTD

Patent Information

Application Number
CN202510293725.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult for existing low-coefficient plastic materials to achieve low friction coefficient, low atomization performance and stable lubrication effects in a wide temperature range at the same time, and have good mechanical properties and environmental adaptability.

Method used

A low-coefficient plastic with low friction coefficient is prepared by using multi-stage responsive three-layer structure microcapsule technology, multi-phase interface regulation and gradient cross-linking network construction. The three-layer structure microcapsules of this material include a core material, an intermediate layer and a shell layer. Through the synergy of multiple lubricating components, controllable release and stability of lubricating performance are achieved.

Benefits of technology

It achieves low friction coefficient (static friction coefficient ≤0.10, dynamic friction coefficient ≤0.08) and low atomization performance (atomization value ≤1.5%), maintains a stable lubrication effect within the temperature range of -40℃ to 150℃, and has excellent mechanical properties and environmental adaptability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of special plastics, in particular to a low-friction-coefficient plastic, a production process and a low-friction-coefficient plastic product, the low-friction-coefficient plastic comprises the following components in parts by weight: 100 parts of a matrix resin system, and the matrix resin system comprises 70-90 parts of polypropylene; 10 to 30 parts of an ethylene-propylene copolymer; 3 to 10 parts of functional microcapsules; 4-12 parts of an interface regulation and control system; according to the low-friction-coefficient plastic, the static friction coefficient is smaller than or equal to 0.10, the dynamic friction coefficient is smaller than or equal to 0.08, meanwhile, the extremely low atomization value is kept to be smaller than or equal to 1.5%, and the extremely low atomization value (smaller than or equal to 1.5%) and the high glossiness retention rate (larger than or equal to 95%) are kept while the low-friction-coefficient plastic obtains excellent friction performance (the static friction coefficient is smaller than or equal to 0.10, and the dynamic friction coefficient is smaller than or equal to 0.08).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of special plastics, and in particular to a low-friction-coefficient plastic, a production process and a low-friction-coefficient plastic product. Background Art

[0002] Low-friction plastic materials are widely used in the fields of automobiles, electronic appliances, medical devices, and aerospace. Especially in the field of automotive interior parts, low-friction plastics can effectively reduce friction between parts, eliminate abnormal noise during movement, and improve the user experience and quality of the product. However, how to ensure the low friction coefficient of the material while meeting the performance requirements of low atomization and high durability has always been a technical challenge faced by this field.

[0003] At present, the methods commonly used in industry to reduce the friction coefficient of plastics mainly include adding lubricants, surface coating treatment and material blending modification. Among them, adding lubricants is the most common and cost-effective method. Traditional lubricants mainly include fatty amides (such as oleamide, stearic acid amide, etc.), fatty acid esters and silicone oils. These lubricants migrate to the surface of the material to form a lubricating film, reducing the friction coefficient of the material.

[0004] However, there are many problems with traditional lubricants during their application: first, lubricants are easy to volatilize at high temperatures, which, on the one hand, causes the lubrication effect to decay over time; on the other hand, the volatiles will condense on cold surfaces (such as car window glass), forming a fogging phenomenon, affecting vision and posing a safety hazard; second, the migration of lubricants is difficult to control, and often excessive migration in the initial stage causes oil overflow, and after long-term use, the lubricant becomes ineffective due to depletion of the lubricant; third, traditional lubricants have limited compatibility with the polymer matrix and are prone to forming independent phases, affecting the mechanical properties and appearance quality of the material.

[0005] In response to the above problems, the industry has proposed a variety of solutions. For example, CN111234387A discloses a low-emission scratch-resistant modified polypropylene. Although the volatility of the material is reduced, the preparation process is complicated and the friction coefficient problem is not solved. CN111320819A discloses a low-cost food-grade self-lubricating polypropylene material, which uses a composite system of high silane coupling agent, lubricant, erucic acid amide, etc. to reduce the friction coefficient, but the precipitation additives used are relatively large, resulting in the problem of precipitation stickiness and unqualified atomization.

[0006] In addition, the existing research on lubricant controlled release systems is mostly focused on the coating technology of a single structure, lacking the fine control of lubricant release dynamics, and not fully considering the continuity and stability of lubrication performance under different temperature conditions. At the same time, the interface compatibility between the lubricating component and the base material, as well as how to maintain the mechanical properties of the material while ensuring low friction performance, are also challenges currently faced by the industry.

[0007] Therefore, there is an urgent need to develop a new type of low friction coefficient plastic material and its preparation method, which can simultaneously achieve low friction coefficient and low atomization performance, maintain a stable lubrication effect in a wide temperature range, and have good mechanical properties and environmental adaptability. Summary of the invention

[0008] The purpose of the present invention is to provide a low friction coefficient plastic, a production process and a low friction coefficient plastic product, aiming to solve the technical problem that it is difficult to achieve both low friction coefficient and low atomization performance in the prior art, while meeting the comprehensive requirements of wide temperature range adaptability, long-term use stability and good mechanical properties.

[0009] The object of the present invention is to provide a low friction coefficient plastic, comprising the following components in parts by weight: 100 parts of a matrix resin system, wherein the matrix resin system comprises: Polypropylene 70-90 parts; 10-30 parts of ethylene propylene copolymer; 3-10 parts of functional microcapsules; Interface regulation system 4-12 copies; and 1-3 parts of multi-stage cross-linking system; The interface control system includes: 2-6 parts of a compatibilizer composite system; 1-4 parts of a nanofiller composite system; 1-2 parts of a functional additive system; The multi-stage cross-linking system comprises: Organic peroxide 0.3-0.8 parts; 0.5-1.5 parts of multifunctional cross-linking monomer; and diallyl phthalate 20% to 40%; And 0.2-0.7 parts of silane crosslinking accelerator.

[0010] Specifically, the functional microcapsule is a three-layer structure microcapsule, and the three-layer structure microcapsule includes: The core material accounts for 50% to 65% of the weight of the microcapsule, and the core material includes: Perfluoropolyether 15% to 25%; Epoxidized soybean oil 25% to 35%; And dimethyl silicone oil 40% to 60%; An intermediate layer, accounting for 20% to 30% of the weight of the microcapsule, wherein the intermediate layer comprises a copolymer of glycidyl methacrylate and methyl methacrylate, wherein the molar ratio of glycidyl methacrylate to methyl methacrylate is 1:2 to 1:5; and an outer shell layer, accounting for 10% to 25% of the weight of the microcapsule, wherein the outer shell layer comprises a crosslinked product of a phosphorus-containing polyurethane polyol and polyisocyanate, wherein the hydroxyl value of the phosphorus-containing polyurethane polyol is 35-60 mg KOH / g, and the phosphorus content of the phosphorus-containing polyurethane polyol is 0.8% to 1.5%.

[0011] Specifically, the compatibilizer composite system includes: Maleic anhydride grafted polypropylene 60% to 80%, wherein the maleic anhydride grafted polypropylene has a maleic anhydride grafting rate of 0.8% to 1.5%; and 20% to 40% of a polyethylene-octene copolymer, wherein the octene content of the polyethylene-octene copolymer is 25% to 35%, and the density of the polyethylene-octene copolymer is 0.86-0.88 g / cm³; The nanofiller composite system comprises: 40% to 60% organic modified montmorillonite, wherein the d-spacing of the organic modified montmorillonite is ≥ 3nm; 20% to 40% nano calcium carbonate, wherein the particle size of the nano calcium carbonate is 20-50 nm and the nano calcium carbonate is treated with stearic acid; and 10% to 30% of bentonite, wherein the bentonite has an aspect ratio of 20-30 and is modified by a silane coupling agent; The functional additive system includes: 40% to 60% of β-cyclodextrin grafted polymer; Antioxidant compound system 20%~40%; And 10% to 20% fluorine-containing silane coupling agent.

[0012] Specifically, the organic peroxide is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, with a purity of ≥90%; The multifunctional cross-linking monomer comprises: Trimethylolpropane trimethacrylate 60%~80%, purity ≥95%; and diallyl phthalate 20% to 40%, purity ≥98%; The silane cross-linking accelerator is 3-mercaptopropyltrimethoxysilane, and the purity is ≥95%.

[0013] Specifically, the preparation method of the β-cyclodextrin grafted polymer comprises the following steps: a) dissolving 10-15 parts by weight of β-cyclodextrin in 80-100 parts by weight of anhydrous dimethyl sulfoxide, stirring and heating to 60-70° C. under nitrogen protection; b) slowly adding 5-8 parts by weight of trimellitic anhydride and stirring the reaction for 8-12 hours; c) pouring the reaction mixture into ice water for precipitation, collecting the product by filtration, washing with acetone for 3-5 times, and vacuum drying at a drying temperature of 50-60° C., a drying pressure of 50-100 Pa, and a drying time of 24 hours to obtain trimellitic anhydride-modified β-cyclodextrin; d) dispersing 5-8 parts by weight of the modified β-cyclodextrin in 100-120 parts by weight of tetrahydrofuran; e) adding 8-12 parts by weight of acrylic acid and 3-5 parts by weight of acrylamide; f) raising the temperature to 65-70°C, adding 0.3-0.5 parts by weight of azobisisobutyronitrile under nitrogen protection; g) After 4-6 hours of reaction, the reaction mixture is poured into excess methanol for precipitation; h) centrifugation at a speed of 3000-4000 rpm for 15-20 minutes, and washing with methanol three times; i) vacuum drying, with a drying temperature of 60-70°C, a drying pressure of 30-50Pa, and a drying time of 48 hours to obtain a β-cyclodextrin grafted polymer with a grafting rate of 40% to 60%.

[0014] Specifically, the preparation method of the three-layer structure microcapsule comprises the following steps: a) 15-25 parts by weight of perfluoropolyether, 25-35 parts by weight of epoxidized soybean oil and 40-60 parts by weight of dimethyl silicone oil are mixed at 75-85° C., 2-3 parts by weight of polyoxyethylene-polyoxypropylene block copolymer is added as an emulsifier, and emulsified for 10-15 minutes in a high-speed disperser at a speed of 4000-6000 rpm to form an O / W emulsion; b) 5-8 parts by weight of glycidyl methacrylate and 15-25 parts by weight of methyl methacrylate are mixed, 0.3-0.5 parts by weight of azo initiator is added, the monomer mixture is slowly added to the above emulsion, stirred at 60-70° C., the stirring speed is 200-300 rpm, and reacted for 3-5 hours under nitrogen protection to form microcapsules coated with the intermediate layer copolymer; c) cooling the reaction system to 30-40°C; d) preparing a shell layer precursor: 15-20 parts by weight of phosphorus-containing polyurethane polyol and 1-2 parts by weight of triphenyl phosphite; e) separately preparing a polyisocyanate solution: dissolving 5-8 parts by weight of a mixture of isomers of hexamethylene diisocyanate in 20-30 parts by weight of ethyl acetate; f) Slowly add the polyisocyanate solution to the dispersion system containing the intermediate layer microcapsules at 30-35°C, with a drop rate of 0.5-1 mL / min; g) Keeping the pH value at 7.5-8.5, reacting for 2-4 hours to form an outer shell layer; h) cooling the product to room temperature and centrifuging at a speed of 2000-3000 rpm for 10-15 minutes; i) Wash with deionized water and ethanol alternately for 3-5 times, freeze-dry at a drying temperature of -40°C, a drying pressure of 10-20 Pa, and a drying time of 24-36 hours to obtain three-layer structure microcapsules.

[0015] A method for preparing the low friction coefficient plastic, the method comprising the following steps: A) Multiphase pretreatment stage, including: A1) Pre-dispersion treatment of nanofillers: organic modified montmorillonite, nano calcium carbonate and bentonite are added to isopropanol in a prescribed proportion with a solid content of 5% to 10%, and dispersed by ultrasonic treatment for 20 to 30 minutes with an ultrasonic power of 300-500W and an ultrasonic frequency of 20-25kHz. A fluorinated silane coupling agent is added in an amount of 1% to 2% of the total filler weight, and reacted at 45-55°C with stirring for 2-3 hours. The mixture is desolvated under reduced pressure at a temperature of 50-60°C and a pressure of 5-10kPa to obtain a surface modified nanofiller composite system; A2) Surface activation treatment of microcapsules: disperse the three-layer microcapsules in n-hexane with a solid content of 10% to 15%, stir at 35-45°C, slowly add silane crosslinking accelerator in an amount of 2% to 4% of the weight of the microcapsules, react for 2-3 hours under an inert atmosphere, collect the product by filtration, and vacuum dry at a drying temperature of 40-50°C, a drying pressure of 100-200 Pa, and a drying time of 12 hours to obtain surface activated microcapsules; A3) Compatibilizer pretreatment: Maleic anhydride grafted polypropylene and polyethylene-octene copolymer are blended in a twin-screw extruder according to the specified ratio, with the temperature zone being 170°C / 180°C / 190°C / 185°C / 175°C and the screw speed being 80-100 rpm; B) Multi-stage reactive extrusion processing stage; C) Gradient-regulated directional processing stage.

[0016] Specifically, the multi-stage reaction extrusion processing stage includes: B1) First stage reactive extrusion: using a co-rotating twin-screw extruder with an L / D ratio of 40:1, the matrix resin and compatibilizer composite system are added to the main feed port according to the formula ratio, and the pre-treated nano-filler composite system is added to the side feed port after the first mixing section. The temperature is divided into 180℃ / 190℃ / 200℃ / 210℃ / 205℃ / 195℃ / 185℃, the screw speed is 150-180rpm, the residence time is 2-3 minutes, and the extrudate is quenched by a water cooling system, and pelletized to obtain a pre-compatibilized material; B2) Second stage reactive extrusion: Pre-compatibilizer, surface activated microcapsules and β-cyclodextrin grafted polymer are added from the main feed port and the side feed port respectively by precise metering, multifunctional cross-linking monomer is added to the special feeding device after the second mixing section, volatiles are removed by vacuuming at the vent before the third mixing section, the vacuum degree is 5-10kPa, the temperature zones are 175℃ / 185℃ / 195℃ / 205℃ / 200℃ / 190℃ / 180℃, the screw speed is 120-150rpm, and the residence time is 3-5 minutes; B3) The third stage of reactive extrusion: the pellets obtained in the second stage are added back into the extruder, and the organic peroxide dispersion is accurately added through the side feed port after the first mixing section through a melt pump. A special screw combination is set up, including high shear mixing elements and low compression ratio conveying elements arranged alternately, the temperature zones are 170℃ / 180℃ / 190℃ / 200℃ / 195℃ / 185℃ / 175℃, the screw speed is 100-130rpm, the residence time is 4-6 minutes, and the extrudate is quenched to below 80℃ through a water cooling system.

[0017] Specifically, the gradient control directional processing stage includes: C1) Electric field assisted directional treatment: The extrudate is passed through a specially designed electric field treatment device in a semi-molten state, with the temperature controlled at 110-130°C, the electric field strength at 1-2kV / cm, the frequency at 50-60Hz, and the treatment time at 30-60 seconds; C2) Gradient cooling molding: A multi-temperature zone cooling system is used to perform gradient cooling on the material. The cooling temperature gradient is 120℃→90℃→60℃→30℃. The cooling rate is controlled to be 5-8℃ / min in the first stage, 8-12℃ / min in the second stage, and 10-15℃ / min in the third stage. The pressure of 10-15MPa is maintained during the cooling process. C3) Post-processing control: The molded material is heat treated in an inert atmosphere at a temperature of 80-90°C for 2-4 hours. After cooling to room temperature, it is precisely cut to obtain the final low friction coefficient composite plastic product.

[0018] A low-friction coefficient plastic product, which is made of the low-friction coefficient plastic or prepared according to the method described.

[0019] The present invention successfully achieves the comprehensive performance optimization of low friction coefficient plastics through innovative multi-level responsive microcapsule technology, multiphase interface regulation, gradient cross-linking network construction and electric field assisted directional treatment, and has the following significant beneficial effects: 1. Synergistic optimization of friction performance and atomization performance: The low friction coefficient plastic of the present invention has excellent friction performance (static friction coefficient ≤ 0.10, dynamic friction coefficient ≤ 0.08) while maintaining an extremely low atomization value (≤ 1.5%) and a high gloss retention rate (≥ 95%). This breakthrough result stems from the innovative design of the three-layer microcapsule: the phosphorus-containing polyurethane network in the outer shell layer provides triple response control of heat / pressure / shear, the glycidyl methacrylate copolymer in the middle layer enhances the interfacial compatibility, and the ternary lubrication system in the core layer realizes the controlled release of the lubricating component. Compared with the traditional lubrication system, the atomization value of the material of the present invention is reduced by about 70%, which completely solves the technical problem of having both low friction coefficient and low atomization performance.

[0020] 2. Excellent temperature adaptability: The ternary lubrication system designed by the present invention achieves stable friction performance in the temperature range of -40°C to 150°C. Test results show that the change rate of the friction coefficient is controlled within 10% after 100 temperature cycles, which is much better than the traditional lubrication system (the change rate is as high as 47%). This wide temperature range adaptability stems from the synergistic mechanism of the three lubricating components: dimethyl silicone oil is the main lubricant in the low temperature zone (-40°C to 20°C), epoxidized soybean oil is the main lubricant in the medium temperature zone (20°C to 80°C), and perfluoropolyether is used to maintain stable performance in the high temperature zone (80°C to 150°C). This design enables the material to adapt to various application scenarios from extremely cold areas to high temperature environments, greatly expanding the application range of the product.

[0021] 3. Excellent long-term use stability: Through 24-hour continuous wear test, the friction coefficient growth rate of the material of the present invention is controlled within 15%, the wear rate is less than 1.5mg / 1000 weeks, and the durability is more than 5 times that of the traditional lubrication system. This excellent long-term stability is attributed to the on-demand release mechanism of the microcapsules: under low stress conditions, the microcapsules remain intact and the material exhibits excellent wear resistance; under high stress conditions, the microcapsules can be controlled to rupture and release lubricating components, replenish the surface lubricating film, and achieve self-repairing function. At the same time, the β-cyclodextrin grafted polymer acts as a molecular recognition unit, which controls the release dynamics of the lubricating molecules through host-guest inclusion, further prolonging the lubrication effect.

[0022] 4. Excellent environmental friendliness: The low friction coefficient plastic of the present invention has extremely low VOC emission (≤30μg / g) and odor level (level 2-3), which is far superior to traditional lubrication systems. This is mainly due to the encapsulation effect of microcapsules and the application of bio-based components such as epoxidized soybean oil. In particular, the epoxidized soybean oil used in the material not only provides good lubrication performance, but also has biodegradability, so that the bio-based content of the final product reaches more than 15%, which meets the increasingly stringent environmental protection requirements and the concept of sustainable development.

[0023] 5. Balance between mechanical properties and friction properties: The present invention successfully solves the contradiction between lubrication properties and mechanical properties in the traditional lubrication system through a carefully designed multiphase interface control system and gradient cross-linked network. Test results show that while maintaining a low friction coefficient, the material exhibits excellent mechanical properties: tensile strength ≥ 36MPa, bending modulus ≥ 1800MPa, and impact strength ≥ 8.2kJ / m². This performance balance is attributed to the reinforcing effect of the nanofiller in the multiphase interface control system and the interface optimization effect of the compatibilizer composite system, as well as the precise structural control of the gradient cross-linked network from the inside to the surface.

[0024] 6. Innovation and practicality of the process: Although the production process of the present invention introduces a number of innovative technologies, the core processing process is still based on traditional melt extrusion molding. The equipment requirements and operation procedures are in line with the actual industrial production, and have good feasibility and promotion value. New process steps such as electric field-assisted directional treatment can be compatible with existing production lines to achieve a smooth transition of technology, which is of great significance for industrial applications.

[0025] In summary, the present invention has comprehensively broken through the technical bottleneck faced by low-friction coefficient plastic materials through the integration and coordination of multiple innovative technologies, and achieved a comprehensive improvement in friction performance, atomization performance, temperature adaptability, durability, environmental friendliness and mechanical properties, opening up new ideas for the design of high-performance functional materials, and has important theoretical value and broad application prospects. DETAILED DESCRIPTION

[0026] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. In the following embodiments, unless otherwise specified, the reagents and materials used can be obtained through commercial channels, and the present embodiments are all completed under laboratory conditions.

[0027] Example 1 The present embodiment provides a low friction coefficient plastic and a production process thereof. The low friction coefficient plastic includes the following components (in parts by weight): 100 parts of a matrix resin system, 3 parts of functional microcapsules, 4 parts of an interface regulation system, and 1 part of a multi-stage cross-linking system.

[0028] The matrix resin system includes: 90 parts of polypropylene (PP 571P of Saudi Basic Industries Corporation, with an isotacticity of 97%, a melt flow rate of 2 g / 10 min, 230°C / 2.16 kg) and 10 parts of ethylene propylene copolymer (ethylene content of 3%, melt flow rate of 10 g / 10 min, 230°C / 2.16 kg).

[0029] The functional microcapsule is a three-layer structure microcapsule, including: a core material (accounting for 65% of the weight of the microcapsule), an intermediate layer (accounting for 20% of the weight of the microcapsule) and an outer shell layer (accounting for 15% of the weight of the microcapsule). The core material includes 25% perfluoropolyether (DuPont's Krytox GPL 107, CAS: 60164-51-4), 35% epoxidized soybean oil (Kehong Chemical's ESBO100, CAS: 8013-07-8) and 40% dimethyl silicone oil (Dow Chemical's XIAMETER PMX-200, viscosity 100cSt, CAS: 63148-62-9); the intermediate layer includes a copolymer of glycidyl methacrylate and methyl methacrylate, the molar ratio of the two is 1:2; the outer shell layer includes a cross-linked product of phosphorus-containing polyurethane polyol and polyisocyanate, wherein the phosphorus-containing polyurethane polyol has a hydroxyl value of 35mg KOH / g and a phosphorus content of 0.8%.

[0030] The interface regulation system comprises: 2 parts of a compatibilizer composite system, 1 part of a nano-filler composite system and 1 part of a functional auxiliary agent system. Among them, the compatibilizer composite system includes 80% maleic anhydride grafted polypropylene (DuPont's Fusabond P353, maleic anhydride grafting rate of 0.8%, CAS: 25722-45-6) and 20% polyethylene-octene copolymer (Dow Chemical's ENGAGE8842, octene content of 25%, density of 0.88g / cm³, CAS: 26221-73-8); the nanofiller composite system includes 60% organic modified montmorillonite (Southern Clay's Cloisite 20A, d-spacing of 3.2nm, CAS: 1318-93-0), 20% nano calcium carbonate (Omya's Omyacarb UFT, particle size of 50nm, treated with stearic acid, CAS: 471-34-1) and 20% bentonite (Tolsa's Pangel S9, aspect ratio of 20, modified with silane coupling agent, CAS: 63800-37-3); the functional additive system includes 60% β-cyclodextrin grafted polymer, 30% antioxidant compound system (Irganox B215 of BASF, composed of 60% octyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 40% tris(2,4-di-tert-butylphenyl) phosphite) and 10% fluorine-containing silane coupling agent (FluoroSyl 8H of Gelman, 1H,1H,2H,2H-perfluorooctyltrimethoxysilane, purity 95%, CAS: 51851-37-7).

[0031] The multi-stage cross-linking system includes: 0.3 parts of organic peroxide (Akzo Nobel Trigonox 101, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, purity 90%, CAS: 78-63-7), 0.5 parts of multifunctional cross-linking monomer and 0.2 parts of silane cross-linking accelerator (Dow Corning Z-6030, 3-mercaptopropyltrimethoxysilane, purity 95%, CAS: 4420-74-0). Among them, the multifunctional cross-linking monomer includes 80% of trimethylolpropane trimethacrylate (TMPTMA of Evonik Industries, purity 95%, CAS: 3290-92-4) and 20% of diallyl phthalate (Satomer SR9016 of Saint-Gobain, purity 98%, CAS: 7659-34-9).

[0032] Preparation method of β-cyclodextrin grafted polymer: 10 parts by weight of β-cyclodextrin were dissolved in 80 parts by weight of anhydrous dimethyl sulfoxide, and the mixture was stirred and heated to 60°C under nitrogen protection; 5 parts by weight of trimellitic anhydride (CAS: 552-30-7) were slowly added, and the mixture was stirred and reacted for 8 hours; the reaction mixture was poured into ice water for precipitation, and the product was collected by filtration; the product was washed with acetone for 3 times, and vacuum dried (50°C, 50Pa) for 24 hours to obtain trimellitic anhydride-modified β-cyclodextrin.

[0033] Disperse 5 parts by weight of the modified β-cyclodextrin in 100 parts by weight of tetrahydrofuran; add 8 parts by weight of acrylic acid and 3 parts by weight of acrylamide; heat to 65°C, add 0.3 parts by weight of azobisisobutyronitrile (AIBN) under nitrogen protection; after reacting for 4 hours, pour the reaction mixture into excess methanol for precipitation; centrifuge (3000 rpm, 15 minutes), wash with methanol 3 times; vacuum dry (60°C, 30Pa) for 48 hours to obtain a β-cyclodextrin grafted polymer with a grafting rate of 40% (determined by thermogravimetric analysis).

[0034] Preparation method of three-layer structure microcapsules: 25 parts by weight of perfluoropolyether, 35 parts by weight of epoxidized soybean oil and 40 parts by weight of dimethyl silicone oil were mixed at 75°C; 2 parts by weight of polyoxyethylene-polyoxypropylene block copolymer (BASF's Pluronic F-127, CAS: 9003-11-6) was added as an emulsifier; and emulsified for 10 minutes at a high-speed disperser (4000 rpm) to form an O / W emulsion.

[0035] 5 parts by weight of glycidyl methacrylate (GMA) and 15 parts by weight of methyl methacrylate (MMA) were mixed, and 0.3 parts by weight of azo initiator (Vazo 67, CAS: 13472-08-7) was added; the monomer mixture was slowly added to the above emulsion, and stirred at 60°C (200 rpm); the mixture was reacted for 3 hours under nitrogen protection to form microcapsules coated with the intermediate layer copolymer.

[0036] The reaction system was cooled to 30°C; a shell layer precursor was prepared: 15 parts by weight of phosphorus-containing polyurethane polyol (Clariant's Exolit OP 550) was added with 1 part by weight of triphenyl phosphite; a polyisocyanate solution was prepared separately: 5 parts by weight of a mixture of isomers of hexamethylene diisocyanate (Bayer MaterialScience's Desmodur N3300, CAS: 28182-81-2) was dissolved in 20 parts by weight of ethyl acetate; the polyisocyanate solution was slowly added dropwise (0.5 mL / min) to the dispersion system containing the intermediate layer microcapsules at 30°C; the pH value was maintained at 7.5 (adjusted with triethylamine) and the reaction was performed for 2 hours to form a shell layer; the product was cooled to room temperature and centrifuged (2000 rpm, 10 minutes); it was washed alternately with deionized water and ethanol for 3 times, and freeze-dried (-40°C, 10 Pa) for 24 hours to obtain a three-layer structure microcapsule, and the final microcapsule had an average particle size of 5 μm (determined by a laser particle size analyzer).

[0037] The low friction coefficient plastic of this embodiment is prepared by the following method: 1) Multiphase pretreatment stage a) Pre-dispersion treatment of nanofillers: organic modified montmorillonite, nano calcium carbonate and bentonite were added to isopropanol in a specified proportion, with a solid content of 5%; ultrasonic treatment (power 300W, frequency 20kHz) was used for dispersion for 20 minutes; fluorine-containing silane coupling agent (1% of the total filler weight) was added, and the mixture was stirred and reacted at 45°C for 2 hours; desolventization was carried out under reduced pressure (50°C, 5kPa) to obtain a surface modified nanofiller composite system; b) Surface activation treatment of microcapsules: disperse the three-layer structure microcapsules in n-hexane with a solid content of 10%; slowly add a silane crosslinking accelerator (2% of the weight of the microcapsules) while stirring at 35°C; react for 2 hours under an inert atmosphere; collect the product by filtration, and vacuum dry it (40°C, 100Pa) for 12 hours to obtain surface activated microcapsules; c) Compatibilizer pretreatment: Maleic anhydride grafted polypropylene and polyethylene-octene copolymer were blended in a twin-screw extruder at a specified ratio, with temperature zones of 170°C / 180°C / 190°C / 185°C / 175°C and a screw speed of 80 rpm.

[0038] 2) Multi-stage reactive extrusion processing stage a) First stage reactive extrusion: using a co-rotating twin-screw extruder with an L / D ratio of 40:1, the matrix resin and compatibilizer composite system are added to the main feed port according to the formula ratio, and the pre-treated nano-filler composite system is added to the side feed port after the first mixing section; the temperature zones are 180°C / 190°C / 200°C / 210°C / 205°C / 195°C / 185°C, the screw speed is 150rpm, and the residence time is 2 minutes; the extrudate is quenched by a water cooling system, pelletized, and a pre-compatibilized material is obtained; b) Second stage reactive extrusion: Pre-compatibilizer, surface activated microcapsules and β-cyclodextrin grafted polymer are added from the main feed port and the side feed port respectively by precise metering; multifunctional cross-linking monomer is added to the special feeding device after the second mixing section; vacuum (5kPa) is drawn at the vent before the third mixing section to remove volatiles; temperature zones are 175℃ / 185℃ / 195℃ / 205℃ / 200℃ / 190℃ / 180℃, screw speed is 120rpm, residence time is 3 minutes; extrusion is carried out through a specially designed die system (die temperature is controlled at 175℃); c) Third stage reactive extrusion: the pellets obtained in the second stage are re-added to the extruder; the organic peroxide dispersion (with carrier resin as the dispersion medium and a concentration of 5%) is accurately added through a melt pump at the side feed port after the first mixing section; a special screw assembly is set, including high shear mixing elements and low compression ratio conveying elements arranged alternately; the temperature zones are 170°C / 180°C / 190°C / 200°C / 195°C / 185°C / 175°C, the screw speed is 100rpm, and the residence time is 4 minutes; the extrudate is rapidly cooled to below 80°C through a water cooling system;

[0039] 3) Gradient control directional processing stage a) Electric field assisted directional treatment: the extrudate is passed through a specially designed electric field treatment device in a semi-molten state (temperature controlled at 110°C); the electric field strength is 1 kV / cm, the frequency is 50 Hz, and the treatment time is 30 seconds; under the action of the electric field, the polar components in the microcapsules form a directional arrangement on the surface of the material; b) Gradient cooling molding: A multi-temperature zone cooling system is used to perform gradient cooling on the material; the cooling temperature gradient is 120℃→90℃→60℃→30℃; the cooling rate is controlled to be 5℃ / min in the first stage, 8℃ / min in the second stage, and 10℃ / min in the third stage; a pressure of 10MPa is maintained during the cooling process to ensure the stability of the internal structure of the material; c) Post-processing control: The molded material is heat treated in an inert atmosphere (80°C, 2 hours); after cooling to room temperature, it is precisely cut to obtain the final low friction coefficient composite plastic product.

[0040] The low-friction plastic prepared by the above method has excellent tribological properties and environmental adaptability. The test results show that its static friction coefficient is 0.08, the dynamic friction coefficient is 0.06, and the atomization value is 1.5%. This is mainly due to the multiple lubrication mechanisms in the three-layer microcapsules: a lasting lubricating film is formed on the surface of the material, and the controllable release of the lubricating components is achieved through the core-shell structure, which effectively solves the problem of easy migration and volatilization of lubricants in traditional low-friction materials. In addition, the synergistic effect of the multiphase interface regulation system and the multi-level cross-linking network enables the material to have excellent mechanical properties and dimensional stability while maintaining low friction performance.

[0041] Example 2 The present embodiment provides a low friction coefficient plastic and a production process thereof. The low friction coefficient plastic includes the following components (in parts by weight): 100 parts of a matrix resin system, 10 parts of functional microcapsules, 12 parts of an interface regulation system, and 3 parts of a multi-stage cross-linking system.

[0042] The matrix resin system includes: 70 parts of polypropylene (PP 571P of Saudi Basic Industries Corporation, with an isotacticity of 96%, a melt flow rate of 8 g / 10 min, 230°C / 2.16 kg) and 30 parts of ethylene propylene copolymer (ethylene content of 8%, melt flow rate of 20 g / 10 min, 230°C / 2.16 kg).

[0043] The functional microcapsule is a three-layer structure microcapsule, including: a core material (accounting for 50% of the weight of the microcapsule), an intermediate layer (accounting for 30% of the weight of the microcapsule) and an outer shell layer (accounting for 20% of the weight of the microcapsule). The core material includes 15% perfluoropolyether, 25% epoxidized soybean oil and 60% dimethyl silicone oil; the intermediate layer includes a copolymer of glycidyl methacrylate and methyl methacrylate, and the molar ratio of the two is 1:5; the outer shell layer includes a cross-linked product of phosphorus-containing polyurethane polyol and polyisocyanate, wherein the hydroxyl value of the phosphorus-containing polyurethane polyol is 60mg KOH / g and the phosphorus content is 1.5%.

[0044] The interface regulation system comprises: 6 parts of a compatibilizer composite system, 4 parts of a nano-filler composite system and 2 parts of a functional auxiliary agent system. Among them, the compatibilizer composite system includes 60% maleic anhydride grafted polypropylene (DuPont's Fusabond P353, maleic anhydride grafting rate of 1.5%, CAS: 25722-45-6) and 40% polyethylene-octene copolymer (Dow Chemical's ENGAGE8842, octene content of 35%, density of 0.86g / cm³, CAS: 26221-73-8); the nanofiller composite system includes 40% organic modified montmorillonite (Southern Clay's Cloisite 20A, d-spacing of 4nm, CAS: 1318-93-0), 40% nano calcium carbonate (Omya's Omyacarb UFT, particle size of 20nm, treated with stearic acid, CAS: 471-34-1) and 20% bentonite (Tolsa's Pangel S9, aspect ratio of 30, modified with silane coupling agent, CAS: 63800-37-3); the functional additive system includes 40% of β-cyclodextrin grafted polymer, 40% of antioxidant compound system (Irganox B215 of BASF, composed of 40% of octyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 60% of tris(2,4-di-tert-butylphenyl) phosphite) and 20% of fluorine-containing silane coupling agent.

[0045] The multi-stage cross-linking system includes: 0.8 parts of organic peroxide (Akzo Nobel Trigonox 101, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, purity 95%, CAS: 78-63-7), 1.5 parts of multifunctional cross-linking monomer and 0.7 parts of silane cross-linking accelerator (Dow Corning Z-6030, 3-mercaptopropyltrimethoxysilane, purity 98%, CAS: 4420-74-0). Among them, the multifunctional cross-linking monomer includes 60% of trimethylolpropane trimethacrylate and 40% of diallyl phthalate.

[0046] Preparation method of β-cyclodextrin grafted polymer: 15 parts by weight of β-cyclodextrin were dissolved in 100 parts by weight of anhydrous dimethyl sulfoxide, and the mixture was stirred and heated to 70°C under nitrogen protection; 8 parts by weight of trimellitic anhydride were slowly added, and the mixture was stirred and reacted for 12 hours; the reaction mixture was poured into ice water for precipitation, and the product was collected by filtration; the product was washed with acetone for 5 times, and vacuum dried (60°C, 100Pa) for 24 hours to obtain trimellitic anhydride-modified β-cyclodextrin.

[0047] 8 parts by weight of the modified β-cyclodextrin are dispersed in 120 parts by weight of tetrahydrofuran; 12 parts by weight of acrylic acid and 5 parts by weight of acrylamide are added; the temperature is raised to 70°C, and 0.5 parts by weight of azobisisobutyronitrile (AIBN) is added under nitrogen protection; after reacting for 6 hours, the reaction mixture is poured into excess methanol for precipitation; centrifugal separation (4000 rpm, 20 minutes), and washed with methanol 3 times; vacuum drying (70°C, 50Pa) for 48 hours to obtain a β-cyclodextrin grafted polymer with a grafting rate of 60% (determined by thermogravimetric analysis).

[0048] Preparation method of three-layer structure microcapsules: 15 parts by weight of perfluoropolyether, 25 parts by weight of epoxidized soybean oil and 60 parts by weight of dimethyl silicone oil were mixed at 85°C; 3 parts by weight of polyoxyethylene-polyoxypropylene block copolymer (BASF's Pluronic F-127, CAS: 9003-11-6) was added as an emulsifier; and emulsified for 15 minutes at a high-speed disperser (6000 rpm) to form an O / W emulsion.

[0049] 8 parts by weight of glycidyl methacrylate (GMA) and 25 parts by weight of methyl methacrylate (MMA) were mixed, and 0.5 parts by weight of azo initiator (Vazo 67, CAS: 13472-08-7) was added; the monomer mixture was slowly added to the above emulsion, and stirred at 70°C (300 rpm); the mixture was reacted for 5 hours under nitrogen protection to form microcapsules coated with the intermediate layer copolymer.

[0050] The reaction system was cooled to 40°C; a shell layer precursor was prepared: 20 parts by weight of phosphorus-containing polyurethane polyol (Clariant's Exolit OP 550) was added with 2 parts by weight of triphenyl phosphite; a polyisocyanate solution was prepared: 8 parts by weight of a mixture of isomers of hexamethylene diisocyanate (Bayer MaterialScience's Desmodur N3300, CAS: 28182-81-2) was dissolved in 30 parts by weight of ethyl acetate; the polyisocyanate solution was slowly added dropwise (1 mL / min) to the dispersion system containing the intermediate layer microcapsules at 35°C; the pH value was maintained at 8.5 (adjusted with triethylamine) and the shell layer was formed after reacting for 4 hours; the product was cooled to room temperature and centrifuged (3000 rpm, 15 minutes); it was washed alternately with deionized water and ethanol for 5 times and freeze-dried (-40°C, 20 Pa) for 36 hours to obtain a three-layer structure microcapsule, and the final microcapsule had an average particle size of 1 μm (determined by a laser particle size analyzer).

[0051] The low friction coefficient plastic of this embodiment is prepared by the following method: 1) Multiphase pretreatment stage a) Pre-dispersion treatment of nanofillers: organic modified montmorillonite, nano calcium carbonate and bentonite were added to isopropanol in a specified proportion, with a solid content of 10%; ultrasonic treatment (power 500W, frequency 25kHz) was used for dispersion for 30 minutes; fluorinated silane coupling agent (2% of the total filler weight) was added, and the mixture was stirred and reacted at 55°C for 3 hours; desolventization was carried out under reduced pressure (60°C, 10kPa) to obtain a surface modified nanofiller composite system; b) Surface activation treatment of microcapsules: disperse the three-layer structure microcapsules in n-hexane with a solid content of 15%; slowly add a silane crosslinking accelerator (4% of the weight of the microcapsules) while stirring at 45°C; react for 3 hours under an inert atmosphere; collect the product by filtration and vacuum dry it (50°C, 200Pa) for 12 hours to obtain surface activated microcapsules; c) Compatibilizer pretreatment: Maleic anhydride grafted polypropylene and polyethylene-octene copolymer were blended in a twin-screw extruder according to a specified ratio, with the temperature partitioning at 170°C / 180°C / 190°C / 185°C / 175°C and the screw speed at 100 rpm;

[0052] 2) Multi-stage reactive extrusion processing stage a) First stage reactive extrusion: using a co-rotating twin-screw extruder with an L / D ratio of 40:1, the matrix resin and compatibilizer composite system are added to the main feed port according to the formula ratio, and the pretreated nano-filler composite system is added to the side feed port after the first mixing section; the temperature zones are 180°C / 190°C / 200°C / 210°C / 205°C / 195°C / 185°C, the screw speed is 180rpm, and the residence time is 3 minutes; the extrudate is quenched by a water cooling system, pelletized, and a pre-compatibilized material is obtained; b) Second stage reactive extrusion: Pre-compatibilizer, surface activated microcapsules and β-cyclodextrin grafted polymer are added from the main feed port and the side feed port respectively by precise metering; multifunctional cross-linking monomer is added to the special feeding device after the second mixing section; vacuum (10kPa) is drawn at the vent before the third mixing section to remove volatiles; temperature zones are 175℃ / 185℃ / 195℃ / 205℃ / 200℃ / 190℃ / 180℃, screw speed is 150rpm, residence time is 5 minutes; extrusion is carried out through a specially designed die system (die temperature is controlled at 185℃); c) Third stage reactive extrusion: the pellets obtained in the second stage are added back into the extruder; the organic peroxide dispersion (with carrier resin as the dispersion medium and a concentration of 10%) is accurately added through a melt pump at the side feed port after the first mixing section; a special screw combination is set up, including high shear mixing elements and low compression ratio conveying elements arranged alternately; the temperature zones are 170°C / 180°C / 190°C / 200°C / 195°C / 185°C / 175°C, the screw speed is 130rpm, and the residence time is 6 minutes; the extrudate is quenched to below 80°C by a water cooling system.

[0053] 3) Gradient control directional processing stage a) Electric field assisted directional treatment: the extrudate is passed through a specially designed electric field treatment device in a semi-molten state (temperature controlled at 130°C); the electric field strength is 2kV / cm, the frequency is 60Hz, and the treatment time is 60 seconds; under the action of the electric field, the polar components in the microcapsules form a directional arrangement on the surface of the material; b) Gradient cooling molding: A multi-temperature zone cooling system is used to perform gradient cooling on the material; the cooling temperature gradient is 120℃→90℃→60℃→30℃; the cooling rate is controlled to be 8℃ / min in the first stage, 12℃ / min in the second stage, and 15℃ / min in the third stage; a pressure of 15MPa is maintained during the cooling process to ensure the stability of the internal structure of the material; c) Post-processing control: The molded material is heat treated in an inert atmosphere (90°C, 4 hours); after cooling to room temperature, it is precisely cut to obtain the final low friction coefficient composite plastic product.

[0054] The low friction coefficient plastic prepared by the above method has better tribological properties and environmental adaptability. The test results show that its static friction coefficient is 0.07, the dynamic friction coefficient is 0.05, and the atomization value is only 0.8%. Compared with Example 1, this embodiment increases the content of microcapsules and the proportion of the interface regulation system, and achieves a lower friction coefficient and better environmental stability through a higher degree of cross-linking and a more perfect interface structure. Especially in high temperature environments (120°C), the material can still maintain good friction properties, which is mainly due to the high temperature stability of perfluoropolyether in the core material and the higher degree of cross-linking of the outer shell layer, so that the microcapsules can maintain structural stability under harsh conditions and achieve long-term lubrication.

[0055] Example 3 This embodiment provides a low friction coefficient plastic and a production process thereof. The low friction coefficient plastic includes the following components (in parts by weight): 100 parts of a matrix resin system, 6 parts of functional microcapsules, 8 parts of an interface regulation system, and 2 parts of a multi-stage cross-linking system.

[0056] The matrix resin system includes: 80 parts of polypropylene (PP 571P of Saudi Basic Industries Corporation, with an isotacticity of 98%, a melt flow rate of 5 g / 10 min, 230°C / 2.16 kg) and 20 parts of ethylene propylene copolymer (ethylene content of 5%, melt flow rate of 15 g / 10 min, 230°C / 2.16 kg).

[0057] The functional microcapsule is a three-layer structure microcapsule, including: a core material (accounting for 55% of the weight of the microcapsule), an intermediate layer (accounting for 25% of the weight of the microcapsule) and an outer shell layer (accounting for 20% of the weight of the microcapsule). The core material includes 20% perfluoropolyether, 30% epoxidized soybean oil and 50% dimethyl silicone oil; the intermediate layer includes a copolymer of glycidyl methacrylate and methyl methacrylate, and the molar ratio of the two is 1:3; the outer shell layer includes a cross-linked product of phosphorus-containing polyurethane polyol and polyisocyanate, wherein the hydroxyl value of the phosphorus-containing polyurethane polyol is 45mg KOH / g and the phosphorus content is 1.2%.

[0058] The interface regulation system comprises: 4 parts of a compatibilizer composite system, 2 parts of a nano-filler composite system and 2 parts of a functional auxiliary agent system. Among them, the compatibilizer composite system includes 70% maleic anhydride grafted polypropylene (DuPont's Fusabond P353, maleic anhydride grafting rate of 1.2%) and 30% polyethylene-octene copolymer (Dow Chemical's ENGAGE 8842, octene content of 30%, density of 0.87g / cm³); the nanofiller composite system includes 50% organic modified montmorillonite (Southern Clay's Cloisite 20A, d-spacing of 3.5nm, CAS: 1318-93-0), 30% nano calcium carbonate (Omya's Omyacarb UFT, particle size of 35nm, treated with stearic acid, CAS: 471-34-1) and 20% bentonite (Tolsa's Pangel S9, aspect ratio of 25, modified with silane coupling agent); the functional additive system includes 50% β-cyclodextrin grafted polymer, 35% antioxidant compound system (BASF's Irganox B215, composed of 50% octyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 50% tris(2,4-di-tert-butylphenyl) phosphite) and 15% fluorinated silane coupling agent (FluoroSyl 8H, 1H,1H,2H,2H-perfluorooctyltrimethoxysilane from Gelman, purity 96%).

[0059] The multi-stage cross-linking system includes: 0.5 parts of organic peroxide (Akzo Nobel Trigonox 101, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, purity 92%, CAS: 78-63-7), 1.0 parts of multifunctional cross-linking monomer and 0.5 parts of silane cross-linking accelerator (Dow Corning Z-6030, 3-mercaptopropyltrimethoxysilane, purity 96%). Among them, the multifunctional cross-linking monomer includes 70% trimethylolpropane trimethacrylate and 30% diallyl phthalate.

[0060] Preparation method of β-cyclodextrin grafted polymer: 12 parts by weight of β-cyclodextrin were dissolved in 90 parts by weight of anhydrous dimethyl sulfoxide, and the temperature was raised to 65°C under stirring under nitrogen protection; 6 parts by weight of trimellitic anhydride were slowly added, and the reaction was stirred for 10 hours; the reaction mixture was poured into ice water for precipitation, and the product was collected by filtration; it was washed with acetone for 4 times, and vacuum dried (55°C, 75Pa) for 24 hours to obtain trimellitic anhydride modified β-cyclodextrin.

[0061] 6 parts by weight of the modified β-cyclodextrin are dispersed in 110 parts by weight of tetrahydrofuran; 10 parts by weight of acrylic acid and 4 parts by weight of acrylamide are added; the temperature is raised to 68°C, and 0.4 parts by weight of azobisisobutyronitrile (AIBN) is added under nitrogen protection; after reacting for 5 hours, the reaction mixture is poured into excess methanol for precipitation; centrifugal separation (3500 rpm, 18 minutes), and washed with methanol 3 times; vacuum drying (65°C, 40Pa) for 48 hours to obtain a β-cyclodextrin grafted polymer with a grafting rate of 50% (determined by thermogravimetric analysis).

[0062] Preparation method of three-layer structure microcapsules: 20 parts by weight of perfluoropolyether, 30 parts by weight of epoxidized soybean oil and 50 parts by weight of dimethyl silicone oil were mixed at 80°C; 2.5 parts by weight of polyoxyethylene-polyoxypropylene block copolymer (BASF's Pluronic F-127, CAS: 9003-11-6) was added as an emulsifier; and emulsification was performed at a high-speed disperser (5000 rpm) for 12 minutes to form an O / W emulsion.

[0063] 6 parts by weight of glycidyl methacrylate (GMA) and 20 parts by weight of methyl methacrylate (MMA) were mixed, and 0.4 parts by weight of azo initiator was added; the monomer mixture was slowly added to the above emulsion, and stirred at 65°C (250rpm); the mixture was reacted for 4 hours under nitrogen protection to form microcapsules coated with the intermediate layer copolymer.

[0064] The reaction system was cooled to 35°C; an outer shell layer precursor was prepared: 18 parts by weight of phosphorus-containing polyurethane polyol (Clariant's Exolit OP 550) was added with 1.5 parts by weight of triphenyl phosphite; a polyisocyanate solution was prepared separately: 6 parts by weight of a mixture of isomers of hexamethylene diisocyanate (Bayer MaterialScience's Desmodur N3300) was dissolved in 25 parts by weight of ethyl acetate; the polyisocyanate solution was slowly added dropwise (0.8 mL / min) to the dispersion system containing the intermediate layer microcapsules at 32°C; the pH value was maintained at 8.0 (adjusted with triethylamine) and the reaction was performed for 3 hours to form an outer shell layer; the product was cooled to room temperature and centrifuged (2500 rpm, 12 minutes); it was washed alternately with deionized water and ethanol for 4 times, and freeze-dried (-40°C, 15 Pa) for 30 hours to obtain a three-layer structure microcapsule, and the final average particle size of the microcapsule was 3 μm (determined by a laser particle size analyzer).

[0065] The low friction coefficient plastic of this embodiment is prepared by the following method: 1) Multiphase pretreatment stage a) Pre-dispersion treatment of nanofillers: organic modified montmorillonite, nano calcium carbonate and bentonite were added to isopropanol in a specified proportion, with a solid content of 7%; ultrasonic treatment (power 400W, frequency 22kHz) was used for dispersion for 25 minutes; fluorinated silane coupling agent (1.5% of the total filler weight) was added, and the mixture was stirred and reacted at 50°C for 2.5 hours; desolventization was carried out under reduced pressure (55°C, 7kPa) to obtain a surface modified nanofiller composite system; b) Surface activation treatment of microcapsules: disperse the three-layer structure microcapsules in n-hexane with a solid content of 12%; slowly add a silane crosslinking accelerator (3% of the weight of the microcapsules) while stirring at 40°C; react for 2.5 hours under an inert atmosphere; collect the product by filtration, and vacuum dry it (45°C, 150Pa) for 12 hours to obtain surface activated microcapsules; c) Compatibilizer pretreatment: Maleic anhydride grafted polypropylene and polyethylene-octene copolymer were blended in a twin-screw extruder at a specified ratio, with temperature zones of 170°C / 180°C / 190°C / 185°C / 175°C and a screw speed of 90 rpm.

[0066] 2) Multi-stage reactive extrusion processing stage a) First stage reactive extrusion: using a co-rotating twin-screw extruder with an L / D ratio of 40:1, the matrix resin and compatibilizer composite system are added to the main feed port according to the formula ratio, and the pretreated nano-filler composite system is added to the side feed port after the first mixing section; the temperature zones are 180°C / 190°C / 200°C / 210°C / 205°C / 195°C / 185°C, the screw speed is 165rpm, and the residence time is 2.5 minutes; the extrudate is quenched by a water cooling system, pelletized, and a pre-compatibilized material is obtained; b) Second stage reactive extrusion: Pre-compatibilizer, surface activated microcapsules and β-cyclodextrin grafted polymer are added from the main feed port and the side feed port respectively by precise metering; multifunctional cross-linking monomer is added to the special feeding device after the second mixing section; vacuum (7kPa) is drawn at the vent before the third mixing section to remove volatiles; temperature zones are 175℃ / 185℃ / 195℃ / 205℃ / 200℃ / 190℃ / 180℃, screw speed is 135rpm, residence time is 4 minutes; extrusion is carried out through a specially designed die system (die temperature is controlled at 180℃); c) Third stage reactive extrusion: the pellets obtained in the second stage are added back into the extruder; the organic peroxide dispersion (with carrier resin as the dispersion medium and a concentration of 7%) is accurately added through a melt pump at the side feed port after the first mixing section; a special screw assembly is set up, including alternating arrangements of high shear mixing elements and low compression ratio conveying elements; the temperature zones are 170°C / 180°C / 190°C / 200°C / 195°C / 185°C / 175°C, the screw speed is 115 rpm, and the residence time is 5 minutes; the extrudate is quenched to below 80°C by a water cooling system.

[0067] 3) Gradient control directional processing stage a) Electric field assisted directional treatment: the extrudate is passed through a specially designed electric field treatment device in a semi-molten state (temperature controlled at 120°C); the electric field strength is 1.5 kV / cm, the frequency is 55 Hz, and the treatment time is 45 seconds; under the action of the electric field, the polar components in the microcapsules form a directional arrangement on the surface of the material; b) Gradient cooling molding: A multi-temperature zone cooling system is used to perform gradient cooling on the material; the cooling temperature gradient is 120℃→90℃→60℃→30℃; the cooling rate is controlled to be 6℃ / min in the first stage, 10℃ / min in the second stage, and 12℃ / min in the third stage; a pressure of 12MPa is maintained during the cooling process to ensure the stability of the internal structure of the material; c) Post-processing control: The molded material is heat treated in an inert atmosphere (85°C, 3 hours); after cooling to room temperature, it is precisely cut to obtain the final low friction coefficient composite plastic product.

[0068] The innovation of this embodiment is that by optimizing the core material ratio and cross-linking density of the three-layer microcapsules, a better balance of temperature adaptability and friction performance is achieved. The test results show that the friction coefficient of the material does not change by more than 15% in the temperature range of -30°C to 100°C, showing excellent temperature stability. This is mainly due to the synergistic effect of the three lubricating components in the core material: dimethyl silicone oil maintains good fluidity at low temperatures, epoxidized soybean oil provides stable lubrication performance in the medium temperature region, and perfluoropolyether is responsible for the lubrication effect in the high temperature region. In addition, the optimized ratio of glycidyl methacrylate to methyl methacrylate in the intermediate layer copolymer (1:3) also forms a stronger interfacial interaction between the microcapsules and the matrix, improving the overall mechanical properties and durability of the material.

[0069] Example 4 The present embodiment provides a low friction coefficient plastic and a production process thereof. The low friction coefficient plastic includes the following components (in parts by weight): 100 parts of a matrix resin system, 5 parts of functional microcapsules, 6 parts of an interface regulation system, and 1.5 parts of a multi-stage cross-linking system.

[0070] The matrix resin system includes: 85 parts of polypropylene (PP 571P of Saudi Basic Industries Corporation, with an isotacticity of 97%, a melt flow rate of 4 g / 10 min, 230°C / 2.16 kg) and 15 parts of ethylene propylene copolymer (ethylene content of 4%, melt flow rate of 12 g / 10 min, 230°C / 2.16 kg).

[0071] The functional microcapsule is a three-layer structure microcapsule, including: a core material (accounting for 60% of the weight of the microcapsule), an intermediate layer (accounting for 22% of the weight of the microcapsule) and an outer shell layer (accounting for 18% of the weight of the microcapsule). Among them, the core material includes 22% perfluoropolyether, 32% epoxidized soybean oil (ESBO 100 of Kehong Chemical, CAS: 8013-07-8) and 46% dimethyl silicone oil (XIAMETER PMX-200 of Dow Chemical, viscosity is 200cSt); the intermediate layer includes a copolymer of glycidyl methacrylate and methyl methacrylate, the molar ratio of the two is 1:4; the outer shell layer includes a cross-linked product of phosphorus-containing polyurethane polyol and polyisocyanate, wherein the phosphorus-containing polyurethane polyol has a hydroxyl value of 50mg KOH / g and a phosphorus content of 1.0%.

[0072] Comparative Example 1 Comparative Example 1 provides a low friction coefficient plastic that does not contain three-layer structure microcapsules, which is composed of: 100 parts of a base resin system (80 parts of polypropylene, with an isotacticity of 97%, a melt flow rate of 4 g / 10 min, 230°C / 2.16 kg; 20 parts of ethylene propylene copolymer, with an ethylene content of 5%, and a melt flow rate of 15 g / 10 min), 2 parts of a traditional lubricant (1.2 parts of oleamide, 0.8 parts of stearamide), 6 parts of an interface regulation system, and 1.5 parts of a multi-stage cross-linking system.

[0073] The preparation method is basically the same as that of Example 3, except that the functional microcapsules are replaced by conventional lubricants, and the preparation and surface activation treatment steps related to the microcapsules are omitted. This comparative example is intended to verify the effect of the three-layer microcapsules of the present invention on the friction performance and environmental adaptability of the material.

[0074] Comparative Example 2 Comparative Example 2 provides a low friction coefficient plastic using single-layer microcapsules, which is composed of: 100 parts of a matrix resin system (the composition is the same as that of Example 1), 5 parts of single-layer structure microcapsules, 4 parts of an interface regulation system, and 1 part of a multi-stage cross-linking system.

[0075] Preparation method of single-layer microcapsules: perfluoropolyether, epoxidized soybean oil and dimethyl silicone oil are mixed at a ratio of 20:30:50 at 80°C; polyvinyl alcohol (completely hydrolyzed type, degree of polymerization of 1700) is added as an emulsifier to prepare an O / W emulsion; melamine and formaldehyde are added under weakly acidic conditions (pH value of 5.5) for in-situ polymerization to form a single-layer shell structure; single-layer microcapsules are obtained by centrifugal separation, washing and drying. This comparative example aims to verify the contribution of the multi-layer microcapsule structure to low friction performance.

[0076] Comparative Example 3 Comparative Example 3 provides a low friction coefficient plastic without electric field assisted orientation treatment, and its formula is exactly the same as that of Example 2, but the electric field assisted orientation treatment step is omitted during the preparation process, and conventional cooling molding is directly performed. This comparative example is intended to verify the effect of electric field assisted orientation technology on microcapsule distribution and material friction performance.

[0077] Comparative Example 4 Comparative Example 4 provides a low friction coefficient plastic without β-cyclodextrin grafted polymer, which is composed of: 100 parts of matrix resin system (the composition is the same as that of Example 3), 6 parts of functional microcapsules (the composition is the same as that of Example 3), 8 parts of the modified interface regulation system and 2 parts of the multi-stage cross-linking system. Among them, the modified interface regulation system does not contain β-cyclodextrin grafted polymer, but is replaced by an increased compatibilizer composite system and an antioxidant composite system. This comparative example is intended to verify the role of β-cyclodextrin grafted polymer in the controlled release of lubricants.

[0078] In order to comprehensively evaluate the performance of the low friction coefficient plastic of the present invention, the following test method is used for systematic testing: 1. Friction coefficient test: The static friction coefficient and dynamic friction coefficient are determined by ASTM D1894 standard method. The specific operation is as follows: the test sample is prepared into a 100mm×200mm×2mm flat plate, and the Universal material testing machine is equipped with a friction coefficient test accessory. The test is carried out at 23±2℃ and relative humidity of 50±5%. The static friction coefficient is measured by a 200g load and the sample is pulled at a speed of 5mm / min; the dynamic friction coefficient is measured by a 200g load and the sample is pulled at a speed of 100mm / min. Each sample is tested 5 times and the average value is taken.

[0079] 2. Atomization test: The atomization performance of the material is tested in accordance with the DIN 75201 test standard (reflection method). The specific method is as follows: Place the sample on an aluminum plate in a glass cover, heat it to 100±2℃, and keep it for 3 hours; measure the degree of light scattering by the condensation on the glass through a photoelectric detector, expressed as a percentage. At the same time, the gloss retention rate of the material is evaluated using the TSM0503G-1997 standard, that is, the gloss ratio of the glass before and after the test. The higher the value, the lower the atomization of the material.

[0080] 3. Temperature resistance test: After the samples were pretreated at -40℃, 23℃, 80℃ and 120℃ for 24 hours, their static friction coefficient was immediately measured; at the same time, the samples were subjected to 100 cycles of temperature change in the range of -40℃ to 120℃ (each cycle included keeping at -40℃ for 2 hours, heating to 120℃ for 2 hours, and then cooling to -40℃), and the rate of change of the friction coefficient before and after the cycle was tested.

[0081] 4. Durability test: The durability test was conducted using the Block-on-Ring friction and wear tester in accordance with the ASTM D3702 standard. The test conditions were: load 5N, rotation speed 200rpm, test time 24 hours, and friction coefficient was measured every 4 hours to evaluate the long-term stability of friction performance. At the same time, the weight loss of the sample before and after the test was measured to calculate the wear rate.

[0082] 5. VOC and odor test: The volatile organic compound (VOC) emission of the material is determined using the VDA 277 standard. The sample is placed in a closed container and kept at 80°C for 2 hours, and the VOC content in the overhead air is analyzed by gas chromatography-mass spectrometry. The odor rating is based on the VDA 270 standard and is scored by 5 trained assessors (1-6, 1 represents no odor, 6 represents an unbearable strong odor).

[0083] 6. Mechanical properties test: tensile strength and elongation at break were measured according to ISO 527, flexural modulus was measured according to ISO 178, and simple beam notched impact strength was measured according to ISO 179. All tests were conducted at 23±2℃ and relative humidity of 50±5%.

[0084] The test results of each embodiment and comparative example are summarized in the following table: Table 1: Friction performance and atomization performance test results

[0085] Table 2: Environmental adaptability test results

[0086] Table 3: Durability and mechanical properties test results

[0087] It can be seen from the test results that the embodiments of the present invention have significant advantages over the comparative examples: Friction performance and atomization performance: The static friction coefficients of Examples 1-4 are all lower than 0.10, and the dynamic friction coefficients are all lower than 0.08, which are significantly better than the comparative examples. At the same time, the atomization values ​​of the examples are all lower than 1.5%, and the gloss retention rate is higher than 95%, which shows that the present invention has successfully solved the technical problem of having both low friction performance and low atomization performance. Compared with comparative example 1, the use of three-layer microcapsules to replace traditional lubricants not only reduces the friction coefficient by about 45%, but also reduces the atomization value by about 70%, which fully proves the superiority of the multi-level responsive microcapsule lubrication system.

[0088] Environmental adaptability: The examples show stable friction performance in a wide temperature range (-40°C to 120°C), and the change rate of the friction coefficient after temperature cycling is less than 10%, while the change rate of Comparative Example 1 is as high as 47%. This fully verifies the temperature adaptability design concept of the ternary lubrication system in the three-layer structure microcapsule: dimethyl silicone oil is used to provide lubrication in the low temperature zone, epoxidized soybean oil is mainly used in the medium temperature zone, and perfluoropolyether is used to maintain stable performance in the high temperature zone. In addition, the VOC emission of the examples is significantly lower than that of the comparative examples, especially compared with Comparative Example 1, which is reduced by about 70%, and the odor level is also controlled at a low level (level 2-3), which is crucial for automotive interior applications.

[0089] Durability and mechanical properties: After a long-term wear test, the friction coefficient growth rate of the embodiment is controlled within 15%, and the wear rate is less than 1.5 mg / 1000 weeks, which is much better than the comparative example. In particular, compared with comparative example 2, the use of three-layer microcapsules instead of single-layer microcapsules improves the durability by about 2 times. This is mainly due to the multi-layer design of the microcapsules. The outer shell layer provides mechanical protection, the middle layer enhances the interface compatibility, and the core layer realizes the controlled release of the lubricating component. More importantly, the embodiment still maintains good mechanical properties while achieving low friction performance, which is attributed to the strengthening effect of the multi-phase interface regulation system.

[0090] Influence of process factors: Comparative Example 3 omitted the electric field assisted orientation treatment step. The results showed that although the basic friction performance was not greatly affected, the durability was significantly inferior to Example 2. After 24 hours, the friction coefficient growth rate increased from 14.3% to 40.0%. This fully proves the importance of electric field assisted orientation treatment for the optimal distribution of microcapsules on the surface of the material. This process step oriented the polar components in the microcapsules to form a more stable lubricating film structure.

[0091] Effect of β-cyclodextrin grafted polymer: β-cyclodextrin grafted polymer was omitted in comparative example 4, and the results showed that the atomization value increased by about 100%, the VOC release increased by about 130%, and the durability decreased significantly. This verifies the important role of β-cyclodextrin grafted polymer as a molecular recognition unit: it can selectively capture lubricating molecules through host-guest inclusion complexes, control their release kinetics, thereby reducing volatility and prolonging the lubrication effect. This precise regulation at the molecular level is one of the core innovations of the present invention.

Claims

1. A low friction coefficient plastic, characterized in that: The low friction coefficient plastic comprises the following components in parts by weight: 100 parts of a matrix resin system, wherein the matrix resin system comprises: Polypropylene 70-90 parts; 10-30 parts of ethylene propylene copolymer; 3-10 parts of functional microcapsules; Interface regulation system 4-12 copies; and 1-3 parts of multi-stage cross-linking system; The interface control system comprises: 2-6 parts of compatibilizer composite system; 1-4 parts of nanofiller composite system; 1-2 parts of functional additive system; The multi-stage cross-linking system comprises: Organic peroxide 0.3-0.8 parts; 0.5-1.5 parts of multifunctional cross-linking monomer; and diallyl phthalate 20% to 40%; And 0.2-0.7 parts of silane crosslinking accelerator.

2. The low friction coefficient plastic according to claim 1, characterized in that: The functional microcapsule is a three-layer structure microcapsule, and the three-layer structure microcapsule comprises: The core material accounts for 50% to 65% of the weight of the microcapsule, and the core material includes: Perfluoropolyether 15% to 25%; Epoxidized soybean oil 25% to 35%; And dimethyl silicone oil 40% to 60%; An intermediate layer, accounting for 20% to 30% of the weight of the microcapsule, wherein the intermediate layer comprises a copolymer of glycidyl methacrylate and methyl methacrylate, wherein the molar ratio of glycidyl methacrylate to methyl methacrylate is 1:2 to 1:5; and an outer shell layer, accounting for 10% to 25% of the weight of the microcapsule, wherein the outer shell layer comprises a crosslinked product of a phosphorus-containing polyurethane polyol and polyisocyanate, wherein the hydroxyl value of the phosphorus-containing polyurethane polyol is 35-60 mg KOH / g, and the phosphorus content of the phosphorus-containing polyurethane polyol is 0.8% to 1.5%.

3. The low friction coefficient plastic according to claim 1, characterized in that: The compatibilizer composite system comprises: Maleic anhydride grafted polypropylene 60% to 80%, wherein the maleic anhydride grafted polypropylene has a maleic anhydride grafting rate of 0.8% to 1.5%; and 20% to 40% of a polyethylene-octene copolymer, wherein the octene content of the polyethylene-octene copolymer is 25% to 35%, and the density of the polyethylene-octene copolymer is 0.86-0.88 g / cm³; The nanofiller composite system comprises: 40% to 60% organic modified montmorillonite, wherein the d-spacing of the organic modified montmorillonite is ≥ 3nm; 20% to 40% nano calcium carbonate, wherein the particle size of the nano calcium carbonate is 20-50 nm and the nano calcium carbonate is treated with stearic acid; and 10% to 30% of bentonite, wherein the bentonite has an aspect ratio of 20-30 and is modified by a silane coupling agent; The functional additive system comprises: β-cyclodextrin grafted polymer 40% to 60%; Antioxidant compound system 20%~40%; And 10% to 20% fluorine-containing silane coupling agent.

4. The low friction coefficient plastic according to claim 1, characterized in that: The organic peroxide is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, with a purity of ≥90%; The multifunctional cross-linking monomer comprises: Trimethylolpropane trimethacrylate 60%~80%, purity ≥95%; and diallyl phthalate 20% to 40%, purity ≥98%; The silane cross-linking accelerator is 3-mercaptopropyltrimethoxysilane, and the purity is ≥95%.

5. The low friction coefficient plastic according to claim 3, characterized in that: The preparation method of the β-cyclodextrin grafted polymer comprises the following steps: a) dissolving 10-15 parts by weight of β-cyclodextrin in 80-100 parts by weight of anhydrous dimethyl sulfoxide, stirring and heating to 60-70° C. under nitrogen protection; b) slowly adding 5-8 parts by weight of trimellitic anhydride and stirring the reaction for 8-12 hours; c) pouring the reaction mixture into ice water for precipitation, collecting the product by filtration, washing with acetone for 3-5 times, and vacuum drying at a drying temperature of 50-60° C., a drying pressure of 50-100 Pa, and a drying time of 24 hours to obtain trimellitic anhydride-modified β-cyclodextrin; d) dispersing 5-8 parts by weight of the modified β-cyclodextrin in 100-120 parts by weight of tetrahydrofuran; e) adding 8-12 parts by weight of acrylic acid and 3-5 parts by weight of acrylamide; f) raising the temperature to 65-70°C, adding 0.3-0.5 parts by weight of azobisisobutyronitrile under nitrogen protection; g) After 4-6 hours of reaction, the reaction mixture is poured into excess methanol for precipitation; h) centrifugation at a speed of 3000-4000 rpm for 15-20 minutes, and washing with methanol three times; i) vacuum drying, with a drying temperature of 60-70°C, a drying pressure of 30-50Pa, and a drying time of 48 hours to obtain a β-cyclodextrin grafted polymer with a grafting rate of 40% to 60%.

6. The low friction coefficient plastic according to claim 2, characterized in that: The preparation method of the three-layer structure microcapsule comprises the following steps: a) 15-25 parts by weight of perfluoropolyether, 25-35 parts by weight of epoxidized soybean oil and 40-60 parts by weight of dimethyl silicone oil are mixed at 75-85° C., 2-3 parts by weight of polyoxyethylene-polyoxypropylene block copolymer is added as an emulsifier, and emulsified for 10-15 minutes in a high-speed disperser at a speed of 4000-6000 rpm to form an O / W emulsion; b) 5-8 parts by weight of glycidyl methacrylate and 15-25 parts by weight of methyl methacrylate are mixed, 0.3-0.5 parts by weight of azo initiator is added, the monomer mixture is slowly added to the above emulsion, stirred at 60-70° C., the stirring speed is 200-300 rpm, and reacted for 3-5 hours under nitrogen protection to form microcapsules coated with the intermediate layer copolymer; c) cooling the reaction system to 30-40°C; d) preparing a shell layer precursor: 15-20 parts by weight of phosphorus-containing polyurethane polyol and 1-2 parts by weight of triphenyl phosphite; e) separately preparing a polyisocyanate solution: dissolving 5-8 parts by weight of a mixture of isomers of hexamethylene diisocyanate in 20-30 parts by weight of ethyl acetate; f) Slowly add the polyisocyanate solution to the dispersion system containing the intermediate layer microcapsules at 30-35°C, with a drop rate of 0.5-1 mL / min; g) Keeping the pH value at 7.5-8.5, reacting for 2-4 hours to form an outer shell layer; h) cooling the product to room temperature and centrifuging at a speed of 2000-3000 rpm for 10-15 minutes; i) Wash with deionized water and ethanol alternately for 3-5 times, freeze-dry at a drying temperature of -40°C, a drying pressure of 10-20 Pa, and a drying time of 24-36 hours to obtain three-layer structure microcapsules.

7. A method for preparing the low friction coefficient plastic according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: A) Multiphase pretreatment stage, including: A1) Pre-dispersion treatment of nanofillers: organic modified montmorillonite, nano calcium carbonate and bentonite are added to isopropanol in a prescribed proportion with a solid content of 5% to 10%, and dispersed by ultrasonic treatment for 20 to 30 minutes with an ultrasonic power of 300-500W and an ultrasonic frequency of 20-25kHz. A fluorinated silane coupling agent is added in an amount of 1% to 2% of the total filler weight, and reacted at 45-55°C with stirring for 2-3 hours. The mixture is desolvated under reduced pressure at a temperature of 50-60°C and a pressure of 5-10kPa to obtain a surface modified nanofiller composite system; A2) Surface activation treatment of microcapsules: disperse the three-layer microcapsules in n-hexane with a solid content of 10% to 15%, stir at 35-45°C, slowly add silane crosslinking accelerator in an amount of 2% to 4% of the weight of the microcapsules, react for 2-3 hours under an inert atmosphere, collect the product by filtration, and vacuum dry at a drying temperature of 40-50°C, a drying pressure of 100-200 Pa, and a drying time of 12 hours to obtain surface activated microcapsules; A3) Compatibilizer pretreatment: Maleic anhydride grafted polypropylene and polyethylene-octene copolymer are blended in a twin-screw extruder according to the specified ratio, with the temperature zone being 170°C / 180°C / 190°C / 185°C / 175°C and the screw speed being 80-100 rpm; B) Multi-stage reactive extrusion processing stage; C) Gradient-regulated directional processing stage.

8. The method according to claim 7, characterized in that The multi-stage reactive extrusion processing stage comprises: B1) First stage reactive extrusion: using a co-rotating twin-screw extruder with an L / D ratio of 40:1, the matrix resin and compatibilizer composite system are added to the main feed port according to the formula ratio, and the pre-treated nano-filler composite system is added to the side feed port after the first mixing section. The temperature is divided into 180℃ / 190℃ / 200℃ / 210℃ / 205℃ / 195℃ / 185℃, the screw speed is 150-180rpm, the residence time is 2-3 minutes, and the extrudate is quenched by a water cooling system, and pelletized to obtain a pre-compatibilized material; B2) Second stage reactive extrusion: Pre-compatibilizer, surface activated microcapsules and β-cyclodextrin grafted polymer are added from the main feed port and the side feed port respectively by precise metering, multifunctional cross-linking monomer is added to the special feeding device after the second mixing section, volatiles are removed by vacuuming at the vent before the third mixing section, the vacuum degree is 5-10kPa, the temperature zones are 175℃ / 185℃ / 195℃ / 205℃ / 200℃ / 190℃ / 180℃, the screw speed is 120-150rpm, and the residence time is 3-5 minutes; B3) The third stage of reactive extrusion: the pellets obtained in the second stage are added back into the extruder, and the organic peroxide dispersion is accurately added through the side feed port after the first mixing section through a melt pump. A special screw combination is set up, including high shear mixing elements and low compression ratio conveying elements arranged alternately, the temperature zones are 170℃ / 180℃ / 190℃ / 200℃ / 195℃ / 185℃ / 175℃, the screw speed is 100-130rpm, the residence time is 4-6 minutes, and the extrudate is quenched to below 80℃ through a water cooling system.

9. The method according to claim 7, characterized in that: The gradient control directional processing stage includes: C1) Electric field assisted directional treatment: The extrudate is passed through a specially designed electric field treatment device in a semi-molten state, with the temperature controlled at 110-130°C, the electric field strength at 1-2kV / cm, the frequency at 50-60Hz, and the treatment time at 30-60 seconds; C2) Gradient cooling molding: A multi-temperature zone cooling system is used to perform gradient cooling on the material. The cooling temperature gradient is 120℃→90℃→60℃→30℃. The cooling rate is controlled to be 5-8℃ / min in the first stage, 8-12℃ / min in the second stage, and 10-15℃ / min in the third stage. The pressure of 10-15MPa is maintained during the cooling process. C3) Post-processing control: The molded material is heat treated in an inert atmosphere at a temperature of 80-90°C for 2-4 hours. After cooling to room temperature, it is precisely cut to obtain the final low friction coefficient composite plastic product.

10. A low friction coefficient plastic product, characterized in that: The low-friction coefficient plastic product is made of the low-friction coefficient plastic described in any one of claims 1 to 6, or is prepared according to the method described in any one of claims 7 to 9.

Citation Information

Patent Citations

  • Low-cost food-grade self-lubricating polypropylene material and preparation method thereof

    CN111320819A

  • Low-friction-coefficient low-atomization polypropylene material as well as preparation method and application thereof

    CN114181453A

  • Fluoropolyether group-containing polymer composition, coating agent, article, and surface modification method for article

    CN118749010A

  • Crosslinked polyethylene self-repairing material with microcapsules in directional distribution under induction of direct-current electric field and preparation method of crosslinked polyethylene self-repairing material

    CN118772504A

Cited By

  • High-weather-resistance and high-dispersion PPR (polypropylene random copolymer) pipeline color master batch and preparation method thereof

    CN121495243A